Path-Following Control of Wheeled Planetary Exploration Robots Moving on Deformable Rough Terrain - Liang Ding; Hai-bo Gao; Zong-quan Deng; Zhijun Li; Ke-rui Xia; Guang-ren Duan (The Scientific World Journal)
The control of planetary rovers, which are high performance mobile robots that move on deformable rough terrain, is a challenging problem. Taking lateral skid into account, this paper presents a rough terrain model and nonholonomic kinematics model for planetary rovers. An approach is proposed in which the reference path is generated according to the planned path by combining look-ahead distance and path updating distance on the basis of the carrot following method. A path-following strategy for wheeled planetary exploration robots incorporating slip compensation is designed. Simulation results of a four-wheeled robot on deformable rough terrain verify that it can be controlled to follow a planned path with good precision, despite the fact that the wheels will obviously skid and slip.